Pendampingan Psikososial Pasca Bencana Banjir Pada Warga Yang Tinggal Di Pinggiran Sungai - Dhian Ririn Lestari; Mutia Rahmah (Universitas Lambung Mangkurat, 2023)
Abstract Populations living in flood-prone areas will experience repeated flood disasters. Flood disasters that occur repeatedly will impact one's health and well-being. Handling the impact of floods, especially psychological impacts such as anxiety, is by providing particular interventions that is called post-flood psychosocial assistance. Community service activities aims to provide participants with knowledge and skills regarding flood disaster preparedness and how to deal with anxiety from flood disasters. The method used is to provide health education and demonstrations and then carry out an evaluation by comparing pretest and posttest scores using a questionnaire. The activity was held in September 2022 and was attended by 19 people. Community service results showed a significant difference in the average value of knowledge before and after being given Disaster Preparedness Education, and participants could overcome anxiety with breathing meditation techniques. Post-flood psychosocial assistance needs to be carried out as a promotive and preventive intervention for communities living in a wetlands area that has the potential to experience repeated floods.Keywords: Psychosocial; Disaster; Flood Abstrak Populasi yang tinggal diarea rawan banjir akan mengalami bencana banjir berulang. Bencana banjir yang terjadi secara berulang akan berdampak pada kesehatan dan kesejahteraan seseorang. Penanganan dampak bencana banjir khususnya dampak psikologis seperti kecemasaan adalah dengan pemberian intervensi khusus berupa pendampingan psikososial pasca bencana banjir. Kegiatan pengabdian masyarakat yang dilakukan bertujuan untuk memberikan pengetahuan dan kemampuan kepada mitra mengenai kesiapsiagaan bencana banjir serta cara mengatasi kecemasan akibat bencana banjir yang terjadi. Metode yang digunakan adalah dengan pemberian pendidikan kesehatan dan demonstrasi kemudian melakukan evaluasi dengan membandingkan nilai pretest dan posttest menggunakan kuesioner. Kegiatan dilaksanakan pada bulan September 2022 dan dihadiri 19 orang. Hasil pengabdian masyarakat menunjukkan terdapat perbedaan yang signifikan pada nilai rerata pengetahuan sebelum dan setelah diberikan Pendidikan Siaga Bencana dan peserta memiliki kemampuan mengatasi kecemasan dengan teknik breathing meditation. Pendampingan psikososial pasca bencana banjir perlu dilakukan sebagai upaya promotif dan preventif masyarakat di lingkungan lahan basah yang berpotensi mengalami bencana banjir berulang. Kata kunci: Psikososial; Bencana; Banjir